Clinical and genetic determinants of chronic visual pathway changes after methanol - induced optic neuropathy: four-year follow-up study. (3rd June 2019) - Nurieva, Olga; Hubacek, Jaroslav A; Urban, Pavel; Hlusicka, Jiri; Diblik, Pavel; Kuthan, Pavel; Sklenka, Petr; Meliska, Martin; Bydzovsky, Jan; Heissigerova, Jarmila; Kotikova, Katerina; Navratil, Tomas; et al.
Abstract: Context: Methanol poisoning induces acute optic neuropathy with possible long-term visual damage. Objective: To study the dynamics and key determinants of visual pathway functional changes during 4 years after acute methanol poisoning. Methods: A total of 42 patients with confirmed methanol poisoning (mean age 45.7 ± 4.4 years) were examined 4.9 ± 0.6, 25.0 ± 0.6, and 49.9 ± 0.5 months after discharge. The following tests were performed: visual evoked potential (VEP), retinal nerve fiber layer (RNFL) measurement, brain magnetic resonance imaging (MRI), complete ocular examination, biochemical tests, and apolipoprotein E (ApoE) genotyping. Results: Abnormal VEP P1 latency was registered in 18/42 right eyes (OD) and 21/42 left eyes (OS), abnormal N1P1 amplitude in 10/42 OD and OS. Mean P1 latency shortening during the follow-up was 15.0 ± 2.0 ms for 36/42 (86%) OD and 14.9 ± 2.4 ms for 35/42 (83%) OS, with maximum shortening up to 35.0 ms. No significant change of mean N1P1 amplitude was registered during follow-up. A further decrease in N1P1 amplitude ≥1.0 mcV in at least one eye was observed in 17 of 36 patients (47%) with measurable amplitude (mean decrease −1.11 ± 0.83 (OD)/−2.37 ± 0.66 (OS) mcV versus −0.06 ± 0.56 (OD)/−0.83 ± 0.64 (OS) mcV in the study population; both p < .001). ApoE4 allele carriers had lower global and temporal RNFL thickness and longer initial P1 latency compared to the non-carriers (all p < .05). The odds ratio for abnormal visual function was 8.92 (3.00–36.50; 95%CI) for ApoE4 allele carriers ( p < .001). The presence of ApoE4 allele was further associated with brain necrotic lesions ( r = 0.384; p = .013) and brain hemorrhages ( r = 0.395; p = .011). Conclusions: Improvement of optic nerve conductivity occurred in more than 80% of patients, but evoked potential amplitude tended to decrease during the 4 years of observation. ApoE4 allele carriers demonstrated lower RNFL thickness, longer P1 latency, and more frequent methanol-induced brain damage compared to non-carriers.